2015
DOI: 10.1016/j.bbagen.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive glycome profiling of Huntington's disease transgenic mice

Abstract: Glycoblotting combined with MALDI-TOF/MS total glycomics warrants a comprehensive, effective, novel and versatile technique for qualitative and quantitative analysis of total glycome expression levels. Furthermore, glycome-focused studies of both environmentally and genetically rooted neurodegenerative diseases are promising candidates for the discovery of potential disease glyco-biomarkers in the post-genome era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 72 publications
(100 reference statements)
2
48
0
Order By: Relevance
“…The GSL‐glycan profile of mouse serum was completely different from that of human, although the serum levels of total GSL‐glycans were almost the same (11.6 ± 4.7 μM in human serum and 11.8 ± 2.1 μM in mouse serum). In mouse serum, 92.8% of the serum GSL‐glycans were GM2 (Hex 2 HexNAc 1 Neu5Gc 1 (GSL‐10)), which agrees well with previous observations . Other components detected in mouse serum include Lc3/asialo‐GM2 (Hex 2 HexNAc 1 , (GSL‐3)), GM3 (Hex 2 Neu5Gc 1 (GSL‐6)), and GSL‐7.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The GSL‐glycan profile of mouse serum was completely different from that of human, although the serum levels of total GSL‐glycans were almost the same (11.6 ± 4.7 μM in human serum and 11.8 ± 2.1 μM in mouse serum). In mouse serum, 92.8% of the serum GSL‐glycans were GM2 (Hex 2 HexNAc 1 Neu5Gc 1 (GSL‐10)), which agrees well with previous observations . Other components detected in mouse serum include Lc3/asialo‐GM2 (Hex 2 HexNAc 1 , (GSL‐3)), GM3 (Hex 2 Neu5Gc 1 (GSL‐6)), and GSL‐7.…”
Section: Resultssupporting
confidence: 90%
“…The serum level of total O‐glycans in mice (C57BL/6J) was estimated to be 33.7 ± 8.24 μM, which is more than 100 times higher than the value recently reported for B6CBAF1 mice (0.32 μM), where O‐glycans were released from glycoproteins by ammonium carbamate . To evaluate this inconsistency, the serum O‐glycome of C57BL/6J mice was analyzed by the method reported in . We found that the amount of O‐glycans released by ammonium carbamate was approximately 100 times lower than that by microwave‐assisted BEP (data not shown).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…On a more global scale, proteomic analyses of AD brains revealed altered glycosylation of 131 GlcNacylation sites in 81 proteins. Another global study comparing brains and sera from HD transgenic mice to controls reveals differences in the levels and pattern of glycans [86]. Aberrant glycosylation of an additional ten glycosylated proteins in several NDs (AD, PD, and HD) was summarized previously [87].…”
Section: Glycosylation/glycationmentioning
confidence: 99%
“…64 O-Glycans were removed with ammonium carbamate at 60 °C for 40 h, followed by washing steps and chemoselective capture on BlotGlyco H hydrazide beads and subsequent derivatizations. The original protocol was developed previously and the authors claim that no significant loss due to peeling was observed.…”
Section: Glycan Release Proceduresmentioning
confidence: 99%